2009
DOI: 10.1002/er.1633
|View full text |Cite
|
Sign up to set email alerts
|

Implications of system expansion for the assessment of well-to-wheel CO2 emissions from biomass-based transportation

Abstract: SUMMARYIn this paper we show the effects of expanding the system when evaluating well-to-wheel (WTW) CO 2 emissions for biomass-based transportation, to include the systems surrounding the biomass conversion system. Four different cases are considered: DME via black liquor gasification (BLG), methanol via gasification of solid biomass, lignocellulosic ethanol and electricity from a biomass integrated gasification combined cycle (BIGCC) used in a battery-powered electric vehicle (BPEV). All four cases are consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 31 publications
0
23
0
3
Order By: Relevance
“…Harvey [11] and Wetterlund et al [20]. It is assumed that the net ows of energy and material entering or Figure 3: Overview of the studied BIGCC biorenery.…”
Section: Evaluation Of Co 2 Emissions and Energy Usementioning
confidence: 99%
See 2 more Smart Citations
“…Harvey [11] and Wetterlund et al [20]. It is assumed that the net ows of energy and material entering or Figure 3: Overview of the studied BIGCC biorenery.…”
Section: Evaluation Of Co 2 Emissions and Energy Usementioning
confidence: 99%
“…Similarly, it is assumed that district heating delivered from the gasication plants in the stand-alone cases replaces alternative district heating production and that DME replaces diesel in heavy trucks. The supply of biomass is regarded as limited, thus additional demand for biomass at the biorenery plant site will lead to increased use of fossil fuels elsewhere in the expanded system, as discussed in reference [20]. The marginal CO 2 eects of increased biomass use are taken into account by assuming an alternative biomass usage.…”
Section: Evaluation Of Co 2 Emissions and Energy Usementioning
confidence: 99%
See 1 more Smart Citation
“…The figures derived from such analyses can be used in subsequent evaluations or as a basis for decision-making. Research has shown that the results of GHG-emission assessments differ, depending on which methods are used and which assumptions about input data are made (e.g., Borrion et al, 2012;Börjesson, 2009;Sjödin and Grönkvist, 2004;Wetterlund et al, 2010). Thus, these results can be difficult to use as they are products of their context.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 presents the renewable energy carriers that were selected and their main production pathway and use. Research has shown that the use of biofuels such as those listed in Table 3 could reduce GHG emissions from transport (see for example Difs et al, 2010;Mohseni et al, 2012;Wetterlund et al, 2010). Great potential has also been identified in the amount of renewable energy that could be used in the transport sector.…”
Section: Renewable Energy Use In Road Transportmentioning
confidence: 99%